A Descriptive Study On English Speaking Teaching-Learning Process At The First Year Of SMP Negeri 02 Colomadu Karanganyar In 2013/2014 Academic Year - Barokah, Novi, Aryati Prasetyarini, S.Pd, M.Pd, Drs. Djoko Srijono, M.Hum (2014)
This research aims at describing English speaking teaching-learning process at the first year of SMP N 2 Colomadu in 2013/2014 academic year. The object of the research is English teaching-learning of speaking at the first year. The subject of this research is the English teacher and the student of VII C class. The writer elaborates six main points concerning how to conduct the research, namely: 1) type of the research is descriptive qualitative research. 2) the object of the research is English teaching-learning of speaking at the first year, 3) the subject of this research is the English teacher and the student of VII C class. 4) the main data of this research are information/ description of the teaching-learning process at the first year of SMP N 02 Colomadu. The sources of data in this research are event, informant, and document. 5) method of collecting data, the writer does some ways in collecting the data such as doing observation, employing interview with student and teacher, and analyzing document. (6) technique for analyzing data, the writer uses interactive model three components of analyzing data, there are: data reduction, data display, and conclusion drawing. Based on the data analysis, the writer finds the implementation of teaching-learning process, consists of the goal of teaching speaking, the material, the teacher's role & learner's role, classroom procedure and evaluation. The writer finds the problem faced by the teacher, namely classroom management, different competences of the students, and the lack of students' activity. The problems faced by the students are limited vocabulary, difficulty of pronunciation, difficulty of structure, and factor nervousness. The problem solving used by the teacher is the teacher always gave advice and motivation to the students about the importance of their activity in speaking class, the teacher created good relation between the teacher and the students, the teacher always gave the remedial to the students who got bad score in speaking test, the teacher suggested to the students in learning English to bring dictionary to find the difficult word and also to add their vocabulary, the students can consult about the difficult material when they have the problem related the lesson or other problems that the student's have.